2015
DOI: 10.1161/circinterventions.114.001441
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Novel Biodegradable Polymer Sirolimus-Eluting Stent With a Durable Polymer Everolimus-Eluting Stent

Abstract: Background-Biodegradable polymers for release of antiproliferative drugs from drug-eluting stents aim to improve vascular healing. We assessed noninferiority of a novel ultrathin strut drug-eluting stent releasing sirolimus from a biodegradable polymer (Orsiro, O-SES) compared with the durable polymer Xience Prime everolimus-eluting stent (X-EES) in terms of the primary end point in-stent late lumen loss at 9 months. Methods and Results-A total of 452 patients were randomly assigned 2:1 to treatment with O-SES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(113 citation statements)
references
References 35 publications
(39 reference statements)
9
102
1
1
Order By: Relevance
“…The observed rate of TVR (5%) in our study was similar to those observed in other large BP-SES studies like the INSPIRE trial (3.9% of TVR) [20] and COMPARE II trial (3.7% of TVR) [16] at 12-month follow-up. Furthermore, the randomised BIOFLOW II trial confirmed promising results of these initial observational studies and presented non-inferiority of BP-SES as compared to everolimus eluting stents [21]. The rate of primary study endpoint (composite of cardiac death, myocardial infarction, and clinically driven TVR) in our study was in line with the COMPARE II trial, in which it occurred in 4.9% of patients at 12-month follow-up [16].…”
Section: (89%)supporting
confidence: 83%
“…The observed rate of TVR (5%) in our study was similar to those observed in other large BP-SES studies like the INSPIRE trial (3.9% of TVR) [20] and COMPARE II trial (3.7% of TVR) [16] at 12-month follow-up. Furthermore, the randomised BIOFLOW II trial confirmed promising results of these initial observational studies and presented non-inferiority of BP-SES as compared to everolimus eluting stents [21]. The rate of primary study endpoint (composite of cardiac death, myocardial infarction, and clinically driven TVR) in our study was in line with the COMPARE II trial, in which it occurred in 4.9% of patients at 12-month follow-up [16].…”
Section: (89%)supporting
confidence: 83%
“…The individual components of the primary end point were numerically higher in diabetic patients treated with BP-SES; however, the difference with the DP-EES group did not reach statistical significance: rates of cardiac death were 3.6% in the BP-SES group and 3.1% in the DP-EES group (HR, 1.18; 95% CI, 0.44-3.16; P=0.74); rates of target-vessel myocardial infarction were 4.9% and 2.7% (HR, 1.83; 95% CI, 0.69-4.88; P=0. 23), and rates of clinically indicated TLR were 6.6% in the BP-SES groups versus 4.5% in the DP-EES group (HR, 1.49; 95% CI, 0.68-3.28; P=0.32), respectively. Although the absolute number of definite ST was higher in diabetic patients treated with BP-SES, no significant differences were recorded between the study arms at different time points.…”
Section: Clinical Outcomes According To Stent Typementioning
confidence: 92%
“…Slower polymer degradation or thinner stent struts may reduce the inflammatory response and the risk of early 29,30 and progressively thinner strut profiles. 13,31,32 Thin stent struts have been associated with less wall shear and thrombogenicity, 33 which may be an explanation for the lower stent thrombosis rate in the SORT OUT VII despite that thinner stent struts may be more prone to longitudinal compression 34 and to an increased risk of tissue prolapse intensifying thrombogenicity. 35 In head-to-head randomized trials, the biodegradable polymer stents have shown noninferiority to the durable flouropolymer everolimus-eluting stent 13,14 and the first-generation sirolimus-eluting stent 15 within the first year after stent implantation, whereas the biolimus-eluting Nobori stent failed to show noninferiority within 1 year in the SORT OUT V trial.…”
Section: Downloaded From Sirolimus-eluting Vs Biolimus-eluting Biodegmentioning
confidence: 99%